La Jul' Shek Sam' Na'i, Class-II - (:unkn) unknown (Odisha School Education Programme Authority Odisha, 2010)
The book is a Language textbook for Class-2.
Keywords: Odia; La Jul' Shek Sam' Na'i; Class-II; Language; Odia; Odia